(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the life, scholarly and pedagogical activities, translation heritage, and contribution of Shoislom Mahmudovich Shomuhamedov, one of the prominent representatives of Uzbek Oriental Studies in the twentieth century. Based on scholarly sources, the study highlights his research on classical Persian-Tajik literature and modern Iranian literature, his achievements in translation studies, and his role in the formation of a scientific school. The scientific novelty of the research lies in the comprehensive analysis of Shomuhamedov’s academic, translation, and pedagogical activities as an integrated system, as well as in identifying his role in the development of the Uzbek school of Oriental Studies through a comparative analysis of relevant sources. The findings demonstrate Shomuhamedov’s significant contribution to the development of Uzbek Oriental Studies and Iranian Studies in the twentieth century, his role in introducing the literary heritage of the East into the Uzbek academic environment, and the importance of his scholarly and pedagogical activities. Furthermore, the study substantiates that his translation of the Shahnameh and his scholarly works had a considerable impact on the development of national culture and translation studies. The scientific and creative legacy of Shoislom Shomuhamedov constitutes an important component of the history of Uzbek Oriental Studies. A thorough investigation of his activities is of considerable theoretical and practical significance for further research in Oriental Studies, Translation Studies, and the history of academic schools.